Profiles of ecotourists' at Mulu National Park based on market segmentation characteristics. - Samdin, Zaiton; Kamaruddin, Norfaryanti; Kamarulzaman, Nitty Hirawaty; Mohd Nawi, Nolila (2012)

(untitled)
Ecotourism is considered the fastest growing market in the tourism industry. Ecotourism is becoming an option for generating more income from the tourism sector particularly for developing countries especially Malaysia. One of the key elements to achieve a viable ecotourism is by tapping the marketing of ecotourism into the right channels and segmenting the right market. This paper describes the profile of ecotourists to Mulu National Park (MNP) based on types of market segmentation in ecotourism. It was found that ecotourists are heterogeneous which denotes that ecotourists' characteristics are diverse in many aspects. Ecotourists are different in their tastes and preferences such as the purpose of visiting and types of attractions offered by the MNP. These kind of information can help park managers to plan better marketing strategies for the long-term sustainable development of the park.